1997
DOI: 10.1016/s0735-1097(96)00568-2
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Response to Exercise After Modified Fontan Operation: Determinants of Performance

Abstract: Subnormal VO2max and HRmax values were demonstrated at peak exercise. Several perioperative variables were associated with VO2max and O2sat at peak exercise. The presence of a classic Glenn anastomosis was associated with decreased O2sat at peak exercise, suggesting intrapulmonary shunting with the classic Glenn anastomosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(66 citation statements)
references
References 22 publications
8
58
0
Order By: Relevance
“…The authors also observed reduced skeletal muscle endurance in a group of seven Fontan patients compared with healthy individuals (15). Some skeletal muscle (75) No change in cardiac output at exercise Grant et al (37) Lower maximal heart rate Brassard et al (15) (75) Higher submaximal heart rate Grant et al (37) Lower arterial blood saturation maximum Brassard et al (15) (75) Lower cardiac output at exercise Durongpisitkul et al (39) alterations encountered in CHF patients, like muscle atrophy and weakness, morphological changes and/or altered metabolic capacity, may explain these results. The authors also observed a significant relationship between skeletal muscle strength and exercise tolerance, suggesting that the skeletal muscle function may be a limiting factor of exercise tolerance in these patients (15).…”
Section: A Forgotten Player: the Peripherymentioning
confidence: 96%
See 3 more Smart Citations
“…The authors also observed reduced skeletal muscle endurance in a group of seven Fontan patients compared with healthy individuals (15). Some skeletal muscle (75) No change in cardiac output at exercise Grant et al (37) Lower maximal heart rate Brassard et al (15) (75) Higher submaximal heart rate Grant et al (37) Lower arterial blood saturation maximum Brassard et al (15) (75) Lower cardiac output at exercise Durongpisitkul et al (39) alterations encountered in CHF patients, like muscle atrophy and weakness, morphological changes and/or altered metabolic capacity, may explain these results. The authors also observed a significant relationship between skeletal muscle strength and exercise tolerance, suggesting that the skeletal muscle function may be a limiting factor of exercise tolerance in these patients (15).…”
Section: A Forgotten Player: the Peripherymentioning
confidence: 96%
“…In fact, 20% of these patients need an antiarrhythmic agent and/or a pacemaker after a mean follow-up of five years (13). Among 59 patients, Durongpisitkul et al (39) reported that 10 patients presented premature ventricular contractions, one patient had ventricular tachycardia, one patient had atrial fibrillation and eight patients had nonspecific ST-T wave changes. However, all these arrhythmias occurred during exercise only, and none were documented during the recovery period (39).…”
Section: Cardiac Arrhythmiasmentioning
confidence: 99%
See 2 more Smart Citations
“…They have been studied and described: patients with Fontan physiology have diminished maximum Vo 2 , 14,15 decreased anaerobic threshold, 14,15 and lower peak heart rate. [15][16][17] The fact that the principal limiting factor (absence of a subpulmonary ventricle) is unalterable has necessarily placed tremendous focus on modifiable factors, including surgical timing, use of a fenestration, PA size, and even the configuration of the Fontan anastomosis. 18 The age at Fontan completion has varied across surgical periods and among institutions.…”
Section: Discussionmentioning
confidence: 99%